IL-7 is a Key Driver Cytokine in Spondyloarthritis? - Rafaela Silva Guimarães Gonçalves; Angela Luzia Branco Pinto Duarte (Journal of Immunology Research)
The rationale for a type 17 signature in the pathogenesis of spondyloarthritis (SpA) has been increasing and being ratified in studies recently. IL-7 is a cytokine whose ability to stimulate IL-17 production in both innate and adaptive immunity cells has made it a promising target not only for a better understanding of the disease as well as an important potential therapeutic target in patients with SpA.